Case Report: Analysis of Preserved Umbilical Cord Clarified X-Linked Anhidrotic Ectodermal Dysplasia With Immunodeficiency in Deceased, Undiagnosed Uncles - Inaba, Satoshi; Aizawa, Yuta; Miwa, Yuki; Imai, Chihaya; Ohnishi, Hidenori; Kanegane, Hirokazu; Saitoh, Akihiko (Frontiers in Immunology, 2021)
Family history is one key in diagnosing inborn errors of immunity (IEI); however, disease status is difficult to determine in deceased relatives. X-linked anhidrotic ectodermal dysplasia with immunodeficiency is one of the hyper IgM syndromes that is caused by a hypomorphic variant in the nuclear factor kappa beta essential modulator. We identified a novel IKBKG variant in a 7-month-old boy with pneumococcal rib osteomyelitis and later found that his mother has incontinentia pigmenti. Genetic analysis of preserved umbilical cords revealed the same variant in two of his deceased maternal uncles. Analysis of preserved umbilical cord tissue from deceased relatives can provide important information for diagnosing IEI in their descendants.